Learning Theories In Instructional Multimedia For English Learning - Farani, Rizki (Journal of English and Education (JEE), 2012)
Learning theory is the concept of human learning. This concept is one of the important components in instructional for learning, especially English learning. English subject becomes one of important subjects for students but learning English needs specific strategy since it is not our vernacular. Considering human learning process in English learning is expected to increase students' motivation to understand English better. Nowadays, the application of learning theories in English learning has appeared in several learning methods and media. One of popular media today is instructional multimedia by using computer. There are many educators who design English material in certain computer software or games. It is still possible to apply learning theories in instructional multimedia program since multimedia provides complete learning by using text, picture, sound, video and animation. Multimedia program can adapt students' differences in learning. It is a good potential of collaborating learning process and technology to learn English better. The program will help students to master the whole English language competence (listening, speaking, reading and writing). This paper will discuss the types of learning theory that can be used in instructional multimedia to learn English. This paper also provides several examples of instructional multimedia product that contain learning theories application.Key Words: Learning theories, Instructional multimedia, English learning